تطبيق ترتيب أسئلة الاختبار على مهارة اللغة الاستقبالية (الإستماع والقرأة) في مدرسة الإبتدائية المتكاملة إقرأ 2 بنجكولو - Agustian Rahmadi; Rahmadani Lubis; Romy Aria Pranata (Universitas Yudharta Pasuruan, 2021)
This study discusses 1) the preparation of open-minded ability questions (Istima and Qiraah) in grade 1 students of SDIT Iqra 2 Bengkulu city. This research uses descriptive qualitative research methods. Data collection is conducted by interview and observation by telephone directly to the teacher concerned. After the collected data is done using: a) reduction of data, b) presentation of data, c) withdrawal of conclusions. From this study can be known that 1) the evaluation system on the receptive language skills of grade 1 students at SDIT Iqra 2 Bengkulu city was conducted during the teaching and learning process and midterm assessment and final semester assessment. The evaluation implementation model was driven by (1) reciting the vocabulary listened (2) identifying the sound (3) the game consisting of: games that attract focus, number games, and guess words. In the student reading evaluation, the teacher presents the assessment with (1) matching the sound and reading (2) assessing the student's reading ability. Evaluation activities carried out by teachers for grade 1 students still need to be developed, such as textbooks that are not adequate for assessing listening and reading skills and the lack of teacher innovation in developing receptive language skills.